Research Status and Development Trends of Deep-sea Unmanned Equipment Control System - Biao WANG; Ruilong LUO; Fang WANG; Weicheng CUI (水下无人系统学报)
Deep-sea unmanned equipment, as a strategic reflection of a nation’s marine scientific and technological strength, has been widely integrated into core fields such as resource exploration, marine scientific research, military security, and economic development. The control system, serving as the neural center for complex underwater operations, directly determines the mission execution efficiency of the equipment. This paper systematically combed the control theory system of deep-sea unmanned equipment, including technical paths such as traditional proportional-integral-derivative (PID) control, model-based control, data-driven intelligent control, and multi-agent control. It deeply analyzed the technical characteristics and engineering applicability of centralized, hierarchical, distributed, and hybrid control architectures. By comparing and analyzing the research status of key technologies such as navigation and positioning, communication transmission, and energy supply, the paper revealed common challenges in the industry, including model uncertainty, robust control performance, and multi-equipment collaboration mechanisms. The study shows that future control systems will develop towards deep empowerment of artificial intelligence, clustered collaborative operations, integration of new communication and energy technologies, and interdisciplinary innovation, providing theoretical and technical support for the intelligent transformation of deep-sea equipment.